2023
DOI: 10.51519/journalisi.v5i1.453
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Recommendation Strategy Based on COBIT 5 For Risk - A Case Study of an Internet Service Provider Company

Abstract: Information technology governance is part of organizational management that includes leadership and ensuring that information technology has a broad scope to meet needs. The concept of IT Governance is a method of managing technology users in. The company, in this case, provides IT needs and solutions to customers ranging from hardware, software, and services. A good business case will include the problem in information technology governance, especially when it comes to maintenance related to POP or Post Offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Qualitative research methods aim to address questions surrounding what, how, and why with regard to a particular phenomenon [8]. In addition, the study collected quantitative data by administering questionnaires to respondents, which were used to calculate capability and maturity levels [8][9][10]. This study has several stage as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative research methods aim to address questions surrounding what, how, and why with regard to a particular phenomenon [8]. In addition, the study collected quantitative data by administering questionnaires to respondents, which were used to calculate capability and maturity levels [8][9][10]. This study has several stage as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of this study is to investigate the beneficial connection between organization, planning, and bank performance. In organizational management, which also includes leadership and ensuring that information technology has a wide range of applications to meet needs, governance is a key component (Setiawan and Fianty, 2023).…”
Section: Planning and Organizing And Bank Performancementioning
confidence: 99%